2020
DOI: 10.33549/physiolres.934641
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of Agrimonia eupatoria L.

Abstract: Agrimonia eupatoria L. is an herb of the Rosaceae family, widely used in traditional (folk) medicine for its beneficial effects. Its water extracts (infusions and decoctions) are used in the treatment of airway and urinary system diseases, digestive tract diseases, and chronic wounds. Phytochemical analyses of Agrimonia eupatoria L. identified a variety of bioactive compounds including tannins, flavonoids, phenolic acids, triterpenoids and volatile oils possessing antioxidant, immunomodulatory and antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…It has been used for gastrointestinal disorders, diarrhea, cholecystitis, pneumonia, hepatopathy, pyelonephritis, cystitis, bleeding disorders, skin defects, and oral mucosal inflammatory diseases [ 13 , 14 ]. The results of published studies have confirmed its anti-inflammatory, astringent, diuretic, antimicrobial, antiviral, antioxidant, neuroprotective, and hepatoprotective effects, as well as many others [ 15 ]. It contains a number of secondary metabolites (polyphenols, tannins, flavonoids) with the ability to reduce silver to nanoscale silver.…”
Section: Introductionmentioning
confidence: 90%
“…It has been used for gastrointestinal disorders, diarrhea, cholecystitis, pneumonia, hepatopathy, pyelonephritis, cystitis, bleeding disorders, skin defects, and oral mucosal inflammatory diseases [ 13 , 14 ]. The results of published studies have confirmed its anti-inflammatory, astringent, diuretic, antimicrobial, antiviral, antioxidant, neuroprotective, and hepatoprotective effects, as well as many others [ 15 ]. It contains a number of secondary metabolites (polyphenols, tannins, flavonoids) with the ability to reduce silver to nanoscale silver.…”
Section: Introductionmentioning
confidence: 90%
“…Scientific reports have indicated that plant products obtained from the aerial parts of Agrimonia eupatoria L. have great pharmaceutical and biological potential, including the recently revealed in vitro anticoagulant activity [16], due to the conjugates of pectin-like polysaccharides with macromolecular polyphenolic matrices. Other well-described small molecule polyphenols from A. eupatoria, including flavonoids, phenolic acids, coumarins, tannins, and terpenoids, have demonstrated beneficial health effects mostly due to their well-known free radical scavenging properties [13,[17][18][19][20][21]. Literature studies have shown that A. eupatoria tissues are especially rich in various flavonoid glycosides, such as luteolin, acacetin, apigenin, quercetin, kaempferol, kaempferide, and rutin [17,[22][23][24], in addition to some flavonols, i.e., catechin, epicatechin and its polymers, myricetin and isorhamnetin, and phenolic acids, i.e., p-coumaric, vanillic, gentisic, p-hydroxybenzoic, and hydroxycinnamic acids [16,17,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The aerial parts harvested from the species Agrimonia eupatoria L. are used in phytotherapy for the treatment of gastrointestinal diseases (gastritis, enteritis, peptic ulcer disease, and nonspecific diarrhea). Additionally, they are used in the treatment of biliary or hepatic disorders [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%